Key Success Factors in Water Management for Sustainability in Phrae Province, Thailand - Nuamcharoen, Suwida; Sattakorn, Wit (European Publisher, 2019)
The research aimed to investigate a case study of water management by the Phrae Provincial Administrative Organization (PAO), which is the major local government in Phrae province in Thailand. The PAO was first runner-up in the Good Governance Awards for Local Government in the Fiscal Year 2018, presented by the Thai Prime Minister’s Office, as a result of demonstrating their innovation in water crisis management. The researchers applied a qualitative research methodology, which consisted of in-depth interviews, group interviews, and non-participatory observation. As a result, the researchers found that the case study proved successful in handling the water crisis in a sustainable way, which led the province towards sustainable development. The PAO established Water Management Schools, which represented self-reliant management to encourage people to co-produce this public service. The literature review, by cross-synthesizing the keywords between the co-production approach and sustainable development, demonstrates the linkage of the two concepts and provides significant keywords. Further, the case study identifies the most outstanding elements that proved to be key success factors in water management for sustainability, namely self-reliance and self-efficiency of the population, democratic participation, community engagement, a collaborative approach and partnership, and a leadership and contingency approach.